Issues in detecting abuse of xenobiotic anabolic steroids and testosterone by analysis of athletes' urine - Catlin, D. H.; Hatton, C. K.; Starcevic, S. H. (Clinical Chemistry, 1997)
Over the last decade the number of laboratories accredited by the International Olympic Committee (IOC) has grown to 25. Nearly half of the ~90 000 samples tested annually are collected on short notice—the most effective means to deter the use of anabolic androgenic steroids (AAS). The major urinary metabolites of AAS have been characterized and are identified by their chromatographic retention times and full or partial mass spectra. The process of determining if an athlete has used testosterone (T) begins with finding a T to epitestosterone (E) ratio >6 and continues with a review of the T/E-time profile. For the user who discontinues taking T, the T/E reverts to baseline (typically ~ 1.0). For the extremely rare athlete with a naturally increased T/E ratio, the T/E remains chronically increased. Short-acting formulations of T transiently increase T/E, and E administration lowers it. Among ancillary tests to help discriminate between naturally increased T/E values and those reflecting T use, the most promising is determination of the carbon isotope ratio.